فاعلية الحجة في الحوار التعليمي بين التنظير ولإجراء - السعيد, قاسمي (جامعة الوادي - University of Eloued, 2021)
فاعلية الحجة في الحوار التعليمي بين التنظير والإجراء The effectiveness of the argument in the educational dialogue between theoretician and the procedure يعد الحوار من بين أهم الاستراتيجيات التواصلية التي تضمن التفاهم والتواصل؛ باعتباره استراتيجية مباشرة وفق ما يقتضيه الموقف وخصوصيته، والخطاب التعليمي واحد من هذه المواقف التواصلية التي تعد الحجة أحد أهم ركائزه، باعتباره حوارا تآزريا إقناعيا يساير فيه المعلم متعلّميه وفق سياقات تواصلية خاصة. بواسطته يمارَس الفعل التعليمي ويحقق هدفه، من أجل توجيه مسارات الفكر وصناعة الرأي. ولمعالجة هذا الموضوع، وجب الإجابة عن الأسئلة الآتية: - ما هي أهم خصوصيات الحوار التعليمي؟ - كيف تساهم الحجة في تحقيق أهدافه؟ - ما الدور المنوط بطرفي هذا الحوار؟ Dialogue is one of the most important communication strategies that ensure understanding and communication as a direct strategy, as required by the situation and its specificity, and the educational discourse is one of these communicative positions, which is one of the most important pillars of the argument, as a synergistic dialogue in which the teacher follows his teacher in accordance with special communication contexts. By doing so, he practices the educational act and achieves its goal, in order to guide the paths of thought and opinion-making. To address this issue, the following questions must be answered: - What are the most important peculiarities of educational dialogue? - How does the argument contribute to its objectives? -What is the role of both sides in this dialogue?
مقال
Keywords: الفاعلية -المعلم – المتعلم -الحوار – الحجة; Effectiveness, teacher, student, dialogue, argument